Demographic responses of rare forest plants to multiple stressors: the role of deer, invasive species and nutrients. (1st July 2014) - Dávalos, Andrea; Nuzzo, Victoria; Blossey, Bernd; Wardle, David
Summary Forest ecosystems in eastern North America face multiple threats or stressors including plant and animal invasions and increased white‐tailed deer (Odocoileus virginianus) herbivory. While each stressor may have independent detrimental effects on native biota, stressors often co‐occur and are likely to have interactive effects. Despite recognition that concurrent processes drive plant demographic responses, few studies evaluate independent and combined effect of stressors. Using a network of 12 sites that varied in non‐native plant cover and introduced earthworm density and biomass, we experimentally assessed effects of deer exclusion (30 × 30 m paired plots), slug exclusion and nutrient addition on survival, growth and fecundity of four rare forest understorey plant species (Aristolochia serpentaria L., Agrimonia rostellata Wallr., Carex retroflexa Muhl. ex Willd and Trillium erectum L). We found that single and combined effects of stressors were species‐specific and varied according to plant stage and demographic parameter. Interactions were prevalent among all studied stressors and, for most cases, did not follow predicted responses. We found detrimental deer herbivory effects on reproductive A. rostellata and non‐consumptive effects on A. serpentaria and T. erectum. Negative deer effects follow underlying predictions, and override effects of other stressors, even when other concurrent processes are at play. Contrary to expectations, we did not find negative effects of non‐native plants. Earthworms had positive effects on A. rostellata and C. retroflexa (especially when deer were excluded), but negative effects on T. erectum. Slug effects were dependent on other stressors, especially on interactions with non‐native plants and earthworms. Nutrient addition had a negative effect on survival of A. serpentaria and T. erectum, but positive effects on C. retroflexa and T. erectum growth. Synthesis. We found prevalent but unpredictable interactions among all study factors and plant species. Negative direct and indirect deer effects overrode impacts of all other stressors we investigated. A multifactor approach is critical to predict plant responses to concurrent environmental forces. Assessment of combined effects should form an essential component of subsequent research on plant demography and management of declining species.